Sed1p and Srl1p are required to compensate for cell wall instability in Saccharomyces cerevisiae mutants defective in multiple GPI-anchored mannoproteins - Hagen, Ilja; Großmann, Guido; Hauser, Nicole; Hoheisel, Jörg D. (Molecular microbiology, 2004)
The covalently linked cell wall protein Ccw12p of Saccharomyces cerevisiae is a GPI-anchored protein (V. Mrsa et al., 1999, J Bacteriol 181: 3076-3086). Although only 121 amino acids long, the haemagglutinin-tagged protein released by laminarinase from the cell wall possesses an apparent molecular mass of >300 kDa. A membrane-bound form with an apparent molecular mass of 58 kDa is highly O- and N-glycosylated and contains the GPI anchor. With a half-life of 2 min, the membrane form is transformed to the >300 kDa form. The deletion mutant ccw12Δ grows slower than the wild type, is highly sensitive to Calcofluor white and contains 2.5 times more chitin. Further, compared with wild-type yeast, significantly more proteins are released from intact cells when treated with dithiothreitol. Interestingly, these defects become less pronounced when further GPI-anchored cell wall proteins are deleted. Mutant ΔGPI (simultaneous deletion of CCW12, CCW13/DAN1, CCW14, TIP1 and CWP1) is similar in many respects to wild-type yeast. To find out how the cell wall is stabilized in mutant ΔGPI, a genome-wide transcription analysis was performed. Of 159 significantly regulated genes, 14 encode either known or suspected cell wall-associated proteins. Analysis of genes affected in transcription revealed that SED1 and SRL1 in particular are required to reconstruct cell wall stability in the absence of multiple GPI-anchored mannoproteins.